Web system of management of household maintenance services for Latin America (Dissertare, 2019)
In the globalized world, society is increasingly immersed in the need for demand or supply of a service. In this context, which is in motion very quickly hand in hand with Information and Communication Technologies (ICT), they play a preeminent role in optimizing the processes and resources of a value chain. In this regard, the aforementioned technologies can offer a significant contribution in the management of services, from the focus of the servuction, which is focused on quality management, as a concept based on customer satisfaction. The present research, of a projective nature, leads to the development of a web portal that, as a university undertaking, automates the management of household maintenance services for the Latin American market, through a modeling that includes artificial intelligence techniques, as a coadjutant to the process optimization. The work is supported by a field design that involves the data collection through direct observation and the application of a digital instrument to a total of 132 heads of family and from there the design of a buyer persona as a strategy of construction of the population ethnography. In the development of the portal, a methodological strategy based on Scrum (Deeme, 2012) is used. The final outcome is a web portal that facilitates the management of service networks, in which all the actors partake in the benefits of an intelligent model of servuction
Keywords: service management; intelligent management model; servuction; artificial intelligence